Fiqh Instruction as a Model for Religious Character Education in Islamic Senior High Schools - Muzahab Badar Ar, Fe Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2025)
Fiqh learning represents a strategic approach to fostering religious character in Islamic senior secondary education. This study aims to examine the implementation of Fiqh learning as a model of religious character education at Madrasah Aliyah NW Darussholihin Darmaji, Central Lombok, as well as to identify supporting and inhibiting factors. Employing a qualitative field study design, data were collected through observation, in-depth interviews, and documentation. Data analysis followed the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that Fiqh learning contributes to students’ religious character formation through the integration of worship practices, moral values, and social responsibility (muamalah) within instructional materials, reinforced by teachers’ exemplary behavior and the habituation of religious activities in the madrasah environment. Teachers’ pedagogical competence and a strong religious culture serve as key supporting factors, while limited instructional time and diverse students’ religious backgrounds remain significant challenges.